2004
DOI: 10.3354/meps275001
|View full text |Cite
|
Sign up to set email alerts
|

Importance of bioturbators for biodiversity maintenance: indirect effects of fishing disturbance

Abstract: The relative impact on macrofaunal diversity of 7 naturally co-occurring bioturbators has been examined in a benthic mesocosm experiment. The bioturbators chosen were selected because of their potential vulnerability to the disturbances associated with demersal trawling. The experiment was conducted at the Solbergstrand mesocosm (Norwegian Institute for Water Research) using subtidal sediment collected from Bjørnehodebukta, a small sheltered bay in the Oslofjord. For 3 of the bioturbating species (Brissopsis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…In Kongfsjord the number of species was highest in a 'transition zone' (the TRANS association), where the fauna consisted of species of both adjacent communities, a pattern consistent with the predictions of the IntermediateDisturbance Hypothesis (Huston 1979). The intermediate levels of bioturbation increase benthic diversity as the depth of oxygenated layers, and thus the effective volume of substrate, is higher in bioturbated sediments (Widdicombe et al 2004). The intermediate levels of physical disturbance of sediments in an Arctic fjord promote the co-existence of tube-building sedentary polychaetes (dominating in the CENTR association) and mobile detritus-feeding bivalves and polychaetes (dominating in the GLAC association, WlodarskaKowalczuk & Pearson 2004), which are likely to compete for space and food in stable conditions (Wilson 1991).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In Kongfsjord the number of species was highest in a 'transition zone' (the TRANS association), where the fauna consisted of species of both adjacent communities, a pattern consistent with the predictions of the IntermediateDisturbance Hypothesis (Huston 1979). The intermediate levels of bioturbation increase benthic diversity as the depth of oxygenated layers, and thus the effective volume of substrate, is higher in bioturbated sediments (Widdicombe et al 2004). The intermediate levels of physical disturbance of sediments in an Arctic fjord promote the co-existence of tube-building sedentary polychaetes (dominating in the CENTR association) and mobile detritus-feeding bivalves and polychaetes (dominating in the GLAC association, WlodarskaKowalczuk & Pearson 2004), which are likely to compete for space and food in stable conditions (Wilson 1991).…”
Section: Discussionsupporting
confidence: 61%
“…Pearson & Rosenberg 1978, Rhoads et al 1978, Aller & Stupakoff 1996, Kaiser et al 2000. Large-bodied, deeply penetrating and effective bioturbators, which often act as structural species by maintaining spatial complexity, are often eliminated (Widdicombe et al 2004). Mean average individual biomass (AIB) was lowest in the glacial bay as the GLAC association was composed of organisms smaller than those found in associations situated further from the glacier.…”
Section: Discussionmentioning
confidence: 99%
“…The decline of these species due to fishing disturbance may have further cascading effects on the diversity and functioning of the entire benthic community. Widdicombe et al (2004) have shown that bioturbating echinoderm species such as Brissopsis lyrifers and Amphiura chiajei, which can be strongly affected by trawling activities, can significantly enhance infaunal diversity. The most important target species for beam trawlers in the southern North Sea (the plaice and the sole), depend on infauna as their main food source (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of biogenic structures can lead to a localized enhancement of meiofaunal (Reise 1983;Alongi 1985;Giere 1993;Austen and Widdicombe 1998) and macrofaunal populations (Rhoads et al 1978;Commito 1982;Flint and Kalke 1986;Tamaki 1988;Posey et al 1991;Widdicombe et al 2004). The walls of open biogenic structures (burrows, tubes, galleries) are key microenvironments for biogeochemical processes as they are the site of exchanges between the ambient sediment and either the organism or water within the structure.…”
mentioning
confidence: 99%